PENINGKATAN KUALITAS BELAJAR BAHASA ARAB DENGAN CARD AND TABLE - Moh. Bachrudin (Universitas Negeri Malang, 2016)
Improving the Arabic Learning Quality of the Seventh Grade Students of Madrasah Tsanawiyah through the Use of Cards and Tables. This action research aimed to improve the Arabic learning quality of Madrasah Tsanawiyah students. The subjects of the study were 39 students of Grade Seven of State Madrasah Tsanawiyah Pare I, Kediri. The instruction was conducted using cards and tables. The data were collected through tests, interviews, observations, and field notes. It was found that the instruction using cards and tables could improve the students' learning activities and results. This was demonstrated by the improvement of students' understanding of language concepts, particularly in speaking and reading comprehension skills.